SPE Annual Technical Conference and Exhibition 2014
DOI: 10.2118/170784-ms
|View full text |Cite
|
Sign up to set email alerts
|

"Slick Water Fracturing and Small Proppant" The future of stimulation or a slippery slope?

Abstract: Over the past 10 years Ely Corp has supervised more than 100,000 "Slick Water Fracture treatments". After more than 30 years of dominance by extremely viscous crosslinked gels, viscous oils, emulsions and foams, the industry has in selection of fracturing fluids, moved to the point that the vast majority of fracturing fluids are either water and friction reducer or combinations of linear gel and or crosslinked gel that is very rapidly degraded to water once in the formation. In a similar time frame our industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…#100 mesh proppant may be an alternative when lager sizes of proppant encounter problems entering narrow and tortuous fractures, as well as ultra-lightweight porous ceramic proppants (Rickards, Brannon and Wood 2013, Ely et al 2014, Alotaibi and Miskimins 2015.…”
Section: Permeability Evolution In Fractures Generated By Comentioning
confidence: 99%
“…#100 mesh proppant may be an alternative when lager sizes of proppant encounter problems entering narrow and tortuous fractures, as well as ultra-lightweight porous ceramic proppants (Rickards, Brannon and Wood 2013, Ely et al 2014, Alotaibi and Miskimins 2015.…”
Section: Permeability Evolution In Fractures Generated By Comentioning
confidence: 99%
“…Some have suggested that in certain cases, proppants aren't necessary to retain open fractures to produce through (Meyerhofer et al, 1997), while others have countered these claims by showing how it is necessary to tailor waterfracs and gel fracs with proppant based on formation properties (Britt et al, 2006). Some have stated how waterfracs and fluid volumes are the driving factor in well production (Ely et al, 2014), while others have shown that proppant volume is a bigger factor than fluid volume (Coulter et al, 2004;Curry and Maloney, 2010;and Nejad et al, 2013). Microseismic fracture monitoring technology has convinced many in the industry that fracture complexity is the normal fracture behavior in shale formations and the concept of stimulated reservoir volume (SRV) was borne out of the desire to use microseismic event data to quantify the volume of formation that has been affected by a stimulation treatment and correlate this volume to well production.…”
Section: Introductionmentioning
confidence: 99%